Nilai Ekonomi Modal Sosial sebagai Media Rekayasa Difusi Teknologi pada Sentra Industri Pangan Skala Kecil - Makhmudun Ainuri (agriTECH, 2009)
The reality showed that in the community of small scale food agroindustry there were many problems. The main prob lem was the technology difusion could not be transferred swimmingly, because social capital of small scale food actors were very weak, and it was only based on material bonds. Based on basic assumptions, economic value assessment of social capital in small scale agroindustries prove that social capital could reduce technology diffusion outlet conges tion, and increase agroindustry endurance and welfare. This research method used Participatory Rapit Appraisal by putting the priority on Focused Group Discussian process, participatory observation, and indepth interview towards facilitators, owners, workers and sellers or consumers of food products. The result of this research showed that the dominan social capital economic value identified were; family relation among agroindustry actors, cooperating in raw material suplying and stocking, products distribution and marketing, agroindustrial networking and sharing of enter prise management information. The contribution values were; labour productivity increase of 1025 % and reduction cost of 12 %, material cost reduction of 5-10 %, increase of marketing efficiency up to 25 %, relative value of group ing and information sharing it could facilitate enterprice acess.  In terms of technology diffution the dominan factors were family relation, community guarantee, institution and communication media, teamworkbased success orienta tion based on trust. The reinforcement of food small scale industry security and technology diffusion could be done (1) reinforcing family relation, (2) reinforcing and developing enterprice grouping based on community education, (3) expanding enterprise group networking by providing social capital, distributor and product marketing, (4) mapping enterprise relations between producers and vendors or suppliers and (5) intensively utilizing facilitators from a variety of sources.ABSTRAKRealitas menunjukkan bahwa masih banyak permasalahan di komunitas agroindustri pangan skala kecil, terutama pada saluran difusi teknologi yang tidak berfungsi secara baik.  Akar penyebabnya diindikasikan karena lemahnya ikatan sosial antar pelaku yang lebih didasarkan atas ikatan material dan menyampingkan modal sosial. Penelusuran nilai ekonomi modal sosial pada agroindustri pangan skala kecil, merupakan bentuk pembuktian atas asumsi dasar bahwa modal social dapat memperbaiki tersumbatnya saluran difusi teknologi, sehingga meningkatkan ketahanan agroindustri yang pada gilirannya dapat menigkatkan kesejahteraan. Metode yang digunakan adalah Participatory Rapit Appraisal dengan mengedepankan proses Focused Group Discusian, observasi partisipatif, dan indept inter view terhadap pendamping, pemilik, pekerja dan penjual atau konsumen. Hasil yang diperoleh menunjukkan bahwa nilai ekonomi modal sosial teridentifikasi pada; hubungan kekerabatan antar pelaku agroindustri, kerjasama dalam pengadaan dan persediaan bahan baku, distribusi dan pemasaran produk, bermitra usaha dan sharing informasi pen gelolaan usaha. Besaran nilai kontribusinya; tenaga kerja terhadap peningkatan produktivitas 10 25 % dan penghe matan biaya 12 %, bahan baku 510 %, pemasaran  sampai 25 %,  berkelompok dan sharing informasi besarannya relatif tetapi memudahkan akses usaha. Faktor difusi teknologinya; hubungan kekerabatan, masyarakat poguyuban (tanggung renteng), tersedianya media komunikasi dan kelembagaan, serta orientasi sukses bersama atas dasar trust. Penguatan   difusi teknologi dan ketahanan agroindustri pangan skala kecil dapat dilakukan dengan memperkuat hubungan kekerabatan, pengembangan kelompok berorientasi usaha sebagai basis sekolah rakyat, memperluas jarin gan kelompok dengan penyedia modal, distributor dan pemasaran produk, memetakan relasi usaha diantara produsen dengan pemasok bahan baku, dan pemanfaatan intensif berbagai  pembinaan dan sumber.